The Influence of Social Media on Public Perception of Crime and Law Enforcement - Kartono; Yanto, Oksidelfa; Salim, Agus (Yayasan Meira Visi Persada, 2025)
This research examines the influence of social media on public perception of crime and law enforcement in the urban communities of Jakarta and South Tangerang. The aim is to analyse how social media shapes the narrative of crime, trust in law enforcement, and public views on legal policies. The method used is qualitative phenomenology with data collection techniques including in-depth interviews, participant observation, and digital document analysis. Data were analysed using the Miles and Huberman model. The research findings indicate that social media plays a significant role in shaping biassed perceptions, creating